2022
DOI: 10.3390/ijerph191610091
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against SARS-CoV-2 in Haemodialysis Patients: Spike’s Ab Response and the Influence of BMI and Age

Abstract: Patients with chronic kidney disease (CKD-5D) in dialysis have been associated with higher rates of SARS-CoV-2 infection. Objective: To identify the CKD-5D patients’ immune system behavior regarding the Pfizer-BioNTech (BNT162b2 mRNA) vaccine (Comirnaty©). This was a multicenter study carried out in 38 dialysis units in NephroCare Portugal. Eligible patients from two cohorts—one composed of completely vaccinated patients with Comirnaty© (vaccinated group) against a second cohort of patients who recovered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Patient antibody levels decreased at a monthly average adjusted rate of 31%, and at six months after vaccination, 40% of patients had either borderline or negative IgG antibodies [ 31 ]. In addition, a study from Portugal showed that elderly patients developed a lower immune response, and the levels of anti-spike IgG antibodies declined faster than in younger patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient antibody levels decreased at a monthly average adjusted rate of 31%, and at six months after vaccination, 40% of patients had either borderline or negative IgG antibodies [ 31 ]. In addition, a study from Portugal showed that elderly patients developed a lower immune response, and the levels of anti-spike IgG antibodies declined faster than in younger patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, the previous humoral response is probably the better predictor of response to successive booster vaccine doses. Additionally, factors such as immunosuppressive drugs or conditions, obesity, older age, absence of previous or breakthrough COVID-19 or lower vaccine dose (number of doses or type of vaccine) can predict a suboptimal immunological response in CKD patients on RRT [ 6 , 8 , 9 , 10 , 27 ]. Thus, these factors should be considered when assessing the risks of not receiving early additional booster vaccine doses.…”
Section: Discussionmentioning
confidence: 99%